﻿Molecular docking investigation of anti-inflammatory herbal compounds as potential LOX-5 and COX-2 inhibitors - Liliia Vyshnevska; Hanna I. Severina; Yuliya Prokopenko; Alexander Shmalko (Pensoft Publishers, 2022)
According to the World Journal of Gastroenterology, more than 5 million people worldwide suffer from inflammatory bowel disease. The use of phytotherapeutic remedies in treatment of chronic inflammatory processes can be an effective alternative in patient's therapy. The advantage of herbal medicines is the ability to influence various links of pathogenesis, lack of addiction, and the absence of withdrawal syndrome with long-term use in chronic pathology. In order to develop a new combined remedy with anti-inflammatory activity for the treatment of colitis, thirteen herbs, which are used in official or traditional medicine in inflammatory processes, were selected among the Ukrainian flora members. To select the most promising drugs and optimize further pharmacological research, molecular docking of the main active substances of the selected herbs to the fundamental pro-inflammatory enzymes - lipoxygenase-5 (LOX-5) and cyclooxygenase-2 (COX-2) - was carried out. Native inhibitors AKBA and celecoxib, respectively, were used as the reference ligands. The selection of candidate structures for in silico research was carried out according to the bibliosemantic research and logical-structural analysis concerning anti-inflammatory effect of the substances, which are part of chemical composition of the selected herbs. Molecular docking results have shown a high affinity level for the active site of the LOX-5 inhibitor gallotannin, quercetin, inulin, sitosterine, and moderate for ellagic acid. High affinity level for the active site of the COX-2 inhibitor was found for inulin, quercetin, gallotannin, ellagic acid and urticin A, moderate one - for gallic acid. For the further pharmacological in vitro and in vivo studies for anti-inflammatory activity, medicinal herbs with the highest content of the mentioned compounds were selected: Inula helenium, Cichorium intybus, Capsella bursa-pastoris, Foeniculum vulgare, Equisetum arvense, Veronica officinalis. Besides, it is recommended to use aqueous extracts of the selected herbs for the further pharmacological studies.